The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/08897077.2017.1356789
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Marijuana, and Opioid use Disorders: 5-Year Patterns and Characteristics of Emergency Department Encounters

Abstract: Background Changes in substance use patterns stemming from opioid misuse, ongoing drinking problems, and marijuana legalization may result in new populations of patients with substance use disorders (SUDs) using emergency department (ED) resources. This study examined ED admission trends in a large sample of patients with alcohol, marijuana, and opioid use disorders in an integrated health system. Methods In a retrospective design, electronic health record (EHR) data identified patients with ≥1 of 3 common S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
(113 reference statements)
2
17
1
3
Order By: Relevance
“…Previous studies in Australia and the United States found similar high levels of emergency department and hospital use among drug users. [7][8][9][10] Although other studies have suggested that people who use drugs visit primary care and preventive health services at lower rates, 8 we found the proportion accessing community physicians to be about the same as matched controls. An important caveat is that about onequarter of community physician visits coincided with periods of opioid agonist therapy (e.g.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Previous studies in Australia and the United States found similar high levels of emergency department and hospital use among drug users. [7][8][9][10] Although other studies have suggested that people who use drugs visit primary care and preventive health services at lower rates, 8 we found the proportion accessing community physicians to be about the same as matched controls. An important caveat is that about onequarter of community physician visits coincided with periods of opioid agonist therapy (e.g.…”
Section: Discussioncontrasting
confidence: 74%
“…14 Substance use and mental health-related concerns were found to be the most common diagnoses during health care visits by people who later overdose, which is consistent with previous studies. 7,15 Of particular note is that diagnoses related to alcohol, stimulant and polysubstance use were frequent in this population, highlighting (as others have found 16,17 ) the role of polysubstance use in predisposing to overdose.…”
Section: Discussionsupporting
confidence: 50%
“…The proportion of participants visiting ED in the past 12 months ranged from 10% to 72% . Studies including relative measures showed frequency of ED utilization of three to 10 times that of comparison groups not using illicit drugs . Exceptions were a study in rural Taiwan, showing that people who inject heroin had a similar rate of ED presentation as the general population , and a study of older people who use cannabis in the United States showing similar odds of ED presentation as those who do not use cannabis .…”
Section: Resultsmentioning
confidence: 99%
“…Les personnes ayant fait une surdose de drogues illicites ont fréquemment utilisé le système de soins de santé au cours de l'année précédant cet événement, comme en témoignent les visites aux services d'urgence, les admissions à l'hôpital et les rendez-vous chez des médecins en milieu communautaire. Des études antérieures menées en Australie et aux États-Unis ont révélé des taux élevés similaires de fréquentation des services d'urgence et des hôpitaux parmi les utilisateurs de drogues [7][8][9][10] . Bien que d'autres études aient laissé entendre que les personnes qui consomment des drogues fréquentent moins les services de soins primaires et de santé préventive 8 , nous avons constaté que la proportion de personnes ayant consulté des médecins en milieu communautaire est à peu près la même que pour les témoins appariés.…”
Section: Analyseunclassified
“…Des problèmes de dépendance et de santé mentale étaient les diagnostics les plus fréquents lors des visites en lien avec des soins de santé effectuées par des personnes qui ont fait une surdose par la suite, ce qui concorde avec certaines études antérieures 7,15 . Il convient de souligner, en particulier, que les diagnostics liés à la consommation d'alcool, de stimulants et de combinaison de plusieurs substances étaient fréquents au sein de cette population, ce qui met en lumière (comme d'autres l'ont constaté 16,17 ) le rôle de la consommation de plusieurs substances combinées dans la prédisposition à une surdose.…”
Section: Analyseunclassified